The Impacts of COVID-19 on Informal Labor Markets : Evidence from Peru - Cueva, Ronald; Del Carpio, Ximena; Winkler, Hernan (World Bank, Washington, DC, 2021)
This paper provides new evidence on the impacts of the COVID-19 economic crisis on a labor market with a high prevalence of informality. The analysis uses a rich longitudinal household survey for Peru that contains a host of individual and job outcomes before and during the first months of the lockdown in 2020. The findings show that workers who had jobs in non-essential and informal sectors were significantly more likely to become unemployed. In contrast to developed countries, having a job amenable to working from home is not correlated with job loss when controlling for informal status. This is consistent with the high level of labor market segmentation observed in Peru, where high-skilled occupations are disproportionately concentrated in the formal sector, which was also better targeted by policies aimed at supporting firms and job protection during the crisis. In addition, the findings show that women were more likely to lose their jobs because female-dominated sectors are more intensive in face-to-face interactions and thereby more affected by social distancing measures. Increased childcare responsibilities also help explain the worse impacts on women in rural areas. Finally, workers who depended on public transportation before the crisis were more likely to lose their jobs during the early months of the pandemic.